2007
DOI: 10.1200/jco.2007.10.8464
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Outcomes From a Randomized Trial of Triple Intrathecal Chemotherapy Compared With 18 Gy Cranial Radiation As CNS Treatment in Acute Lymphoblastic Leukemia: Findings From Dana-Farber Cancer Institute ALL Consortium Protocol 95-01

Abstract: This randomized trial revealed only subtle differences 6 years after diagnosis between children who received CNS therapy as CRT plus double IT drug or as intensive triple IT drug. In most situations where comparable therapeutic efficacy can be achieved without CRT, it is preferable to do so. Where therapeutically necessary, however, CRT at lower doses may not add risk for significant neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 36 publications
3
57
0
Order By: Relevance
“…Even when intelligence in both groups was average, memory or academic achievement was lower in the CR group [Mulhern et al, 1988;Mulhern et al, 1991;Waber et al, 1995;Reddick et al, 2006]. Waber et al [2007] did not find a difference in estimated intelligence between CR and CO groups, but the CR group showed reduced naming speed and parentreport of poorer adaptive skills. However, other studies did not find meaningful differences between CR and CO groups Giralt et al, 1992] and the authors speculate that the agents used, dose, or timing of chemotherapy contributed to their discrepant findings.…”
Section: Radiation Versus Chemotherapy-onlymentioning
confidence: 65%
See 1 more Smart Citation
“…Even when intelligence in both groups was average, memory or academic achievement was lower in the CR group [Mulhern et al, 1988;Mulhern et al, 1991;Waber et al, 1995;Reddick et al, 2006]. Waber et al [2007] did not find a difference in estimated intelligence between CR and CO groups, but the CR group showed reduced naming speed and parentreport of poorer adaptive skills. However, other studies did not find meaningful differences between CR and CO groups Giralt et al, 1992] and the authors speculate that the agents used, dose, or timing of chemotherapy contributed to their discrepant findings.…”
Section: Radiation Versus Chemotherapy-onlymentioning
confidence: 65%
“…Because children with ALL are treated according to risk-stratified protocols, random assignment is only ethical within risk-stratified cohorts [see MacLean et al, 1995;Waber et al, 2004Waber et al, , 2007. Investigation of the role of demographic variables (e.g., age, sex) on neurocognitive outcomes is complicated by the fact that these same variables are often used in the initial risk stratification and, inevitably, are confounded with treatment.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…However, CRT is associated with significant side effects, including cognitive, endocrine, and growth dysfunction, as well as secondary malignancies. [2][3][4] Studies have indicated that patients with B-precursor ALL who are CNS1 (Ͻ5 WBC/L and no blasts on cytospin) or CNS2 (Ͻ5 WBC/L and blasts on cytospin) may be successfully treated without CRT. In these trials, CRT is typically replaced with extra doses of intrathecal chemotherapy and/or medium-or high-dose intravenous methotrexate.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological testing performed 6 years after diagnosis found that cognitive function was in the average range for both patient groups. 2 Historically, T-cell ALL (T-ALL) patients have been considered to be at higher risk of CNS relapse and have received CRT as CNS prophylaxis, but some recent trials have omitted CRT for this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have been inconsistent with regard to the affected domains and their degree of impairment, especially those that result from intrathecal chemotherapy used to prevent infiltration of neoplastic cells into the CNS. Additionally, few studies have used controlled experimental designs, reflected by the variability of the tests used and the limited availability of tools that evaluate children and the multifactorial aspects of the pathology and modern treatment protocols (Waber et al, 2007).…”
Section: Introductionmentioning
confidence: 99%